2022
DOI: 10.1021/acsbiomaterials.2c00596
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Bone Regeneration by an Astaxanthin-Modified Antioxidant Aerogel through Relieving Oxidative Stress via the NRF2 Signaling Pathway

Abstract: Bone regeneration of critical-sized bone defects (CSBDs) with biomimetic collagen-based aerogels remains a significant challenge due to the oxidative stress on the microenvironment. The excessive oxidative stress could induce apoptosis and dysfunction of host-derived cells. Astaxanthin (ATX) exhibits excellent antioxidant ability to block free radical chain reactions. In the present study, hybrid antioxidant collagen-derived aerogels (ATX–Col aerogels) were fabricated by a simple one-step method through the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…[29] Therefore, sufficient antioxidant was needed to compete against oxidative damage and protect the growth of new tissues. [30,31] Accordingly, it suggested that Co-ClAP/PLGA scaffolds removed excess ROS in osteochondral defects, maintained a beneficial regeneration microenvironment, regulated the immune microenvironment, thereby promoting the integrated regeneration of articular cartilage and subchondral bone.…”
Section: In Vivo Osteochondral Regenerative Effects Of the Composite ...mentioning
confidence: 99%
“…[29] Therefore, sufficient antioxidant was needed to compete against oxidative damage and protect the growth of new tissues. [30,31] Accordingly, it suggested that Co-ClAP/PLGA scaffolds removed excess ROS in osteochondral defects, maintained a beneficial regeneration microenvironment, regulated the immune microenvironment, thereby promoting the integrated regeneration of articular cartilage and subchondral bone.…”
Section: In Vivo Osteochondral Regenerative Effects Of the Composite ...mentioning
confidence: 99%
“…Though bone is a dynamic tissue that is able to continuously remodel, and also to repair itself in case of injury, some traumatic and pathologic lesions are so extensive that they exceed the organism’s regeneration capacity [ 12 , 13 , 14 , 15 , 16 ]. Moreover, with an increasingly aging world population, and increased demand for higher health standards and quality of life, it has become imperative to develop strategies to overcome bone regeneration obstacles [ 12 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with an increasingly aging world population, and increased demand for higher health standards and quality of life, it has become imperative to develop strategies to overcome bone regeneration obstacles [ 12 , 17 , 18 , 19 ]. Since there are limitations to the use of autografts and allografts for surgical filling of large bone void defects [ 14 , 15 , 16 , 18 , 19 , 20 ], in recent decades, bone tissue engineering has been developing biomimetic alloplastic graft biomaterials inspired by the above-mentioned macro and microstructure of bone, as well as by its ECM physicochemical features [ 2 , 11 , 13 , 14 , 16 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation